Altered primary CD8+ T cell response to a modified virus Ankara(MVA)-vectored vaccine in the absence of CD4+ T cell help. - Estcourt, M; Mcmichael, A; Hanke, T (2005)
T cell receptor-transgenic F5 mice were used to assess primary CD8+ T cell responses to a modified virus Ankara (MVA)-vectored vaccine in the absence of CD4+ T cell help. Naive, CD8-enriched, CFSE-labelled F5 cells were transferred into normal or CD4+ cell-depleted mice and the mice were vaccinated with MVA.HIVA-NP. At different time points during the primary response, F5 cells were re-isolated and analysed on divisional basis for a number of parameters. We demonstrated that the primary CD8+ T cell response in the absence of CD4+ T cell help differed from that in normal CD4+ cell-undepleted mice. While in the absence of CD4+ T cell help, the initial migratory progress from the local response to a systemic one was not grossly affected, the proportion of dying F5 cells during the expansion phase was markedly increased and resulted in an overall smaller expansion and significantly decreased frequency of CD8+ T cell memory after contraction. T cells primed without help displayed accelerated proliferation and activation, while expression of interferon-gamma remained similar. These phenomena were observed in the lymph nodes draining the MVA.HIVA-NP immunization site and were similar, but delayed by 2-3 days in spleen and non-draining lymph nodes.